2013
DOI: 10.1111/j.1747-4469.2012.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making in a Hybrid Organization: A Case Study of a Southwestern Drug Court Treatment Program

Abstract: This article presents a case study of decision making in a drug court located the southwestern United States. This study seeks to fill a gap in research on decision making by attending to the ways that drug court officials navigate the demands of a court that is dedicated to both therapy and criminal justice. This analysis differs from previous research by viewing the drug court as a "hybrid organization" and asking how the staff members interact in the decision-making process. Additionally, this research prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Individuals emerge in this study as a key site of institutional competition, a position they have rarely received adequate credit for in the institutional and socio‐legal literature. Past studies primarily demonstrate how institutional competition is resolved at the organizational level through an intra‐organizational or inter‐individual division of labor whereby those who adhere to different logics take on different roles in the organization (Nelson and Nielsen 2000; Reay and Hinings 2009; Dunn and Jones 2010; Castellano 2011; Baker 2012) or negotiate institutional problems as organizational ones (Heimer 1999; Binder 2007). However, these tactics are unavailable to individual workers who face competing institutional demands, requiring them to engage in other processes, such as those demonstrated here.…”
Section: Situating Frontline Work Within An Inter‐institutional Systemmentioning
confidence: 99%
“…Individuals emerge in this study as a key site of institutional competition, a position they have rarely received adequate credit for in the institutional and socio‐legal literature. Past studies primarily demonstrate how institutional competition is resolved at the organizational level through an intra‐organizational or inter‐individual division of labor whereby those who adhere to different logics take on different roles in the organization (Nelson and Nielsen 2000; Reay and Hinings 2009; Dunn and Jones 2010; Castellano 2011; Baker 2012) or negotiate institutional problems as organizational ones (Heimer 1999; Binder 2007). However, these tactics are unavailable to individual workers who face competing institutional demands, requiring them to engage in other processes, such as those demonstrated here.…”
Section: Situating Frontline Work Within An Inter‐institutional Systemmentioning
confidence: 99%
“…Scholars have noted that this mode of intervention relies on relationships between drug court professionals and clients that are like those between parents and children. In her study of decision-making processes in a drug court, Baker (2013) found that relations in the court are not as collaborative as the "team" metaphor suggests. Instead, she likened the relationships among professionals to those characterizing the patriarchal family.…”
Section: Drug Treatment Courts and The Family Frameworkmentioning
confidence: 99%
“…Research on drug courts has found that judges routinely use “tough love” (Burns and Peyrot 2003) jail sanctions, also called shock incarceration or flash incarceration , for clients who fail to conform to the behavioral expectations of the program (Nolan 2001; Griffin, Steadman, and Petrila 2002; Baker 2013). MHC judges, however, are keenly aware that using incarceration as a “brute force” (Kleiman 2009) response to program noncompliance is not always a necessary or even morally appropriate way to advance the court's objectives for persons with severe mental illnesses.…”
Section: Crafting Problem-solving Justicementioning
confidence: 99%
“…The first lesson we can learn from this study is that while most sociological studies of PSCs explore how justices grapple with the opposing logics of treatment and punishment to advance the court's objectives (see Burns and Peryot 2003, 2008; Paik 2011; Baker 2013; Lyons 2013), the construct of benchcraft allows scholars to move beyond the “carrot and stick” approach to program compliance, and focus on other dimensions of judicial behavior in MHCs. Specifically, the data reveal that judges engage in a kind of bricolage (Levi-Strauss [1962] 1966).…”
Section: Conclusion: the Politics Of Benchcraftmentioning
confidence: 99%